2008
DOI: 10.1039/b806016a
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear chiral vanadium catalysts for oxidative coupling of 2-naphthols via a dual activation mechanism

Abstract: This review describes our recent efforts in the development of chiral dinuclear vanadium complexes that work as dual activation catalysts for the oxidative coupling of 2-naphthols. The dinuclear vanadium(iv) complex (R(a),S,S)- was prepared by complexation of VOSO(4) with the Schiff base derived from (R)-3,3'-diformyl-2,2'-dihydroxy-1,1'-binaphthyl () and (S)-tert-leucine. Since the dinuclear vanadium(iv) complex was found to be readily oxidized to afford a corresponding vanadium(v) species during preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 78 publications
1
49
0
Order By: Relevance
“…Related to Gong's catalyst 26, Sasai and coworkers [54][55][56][57] described dinuclear vanadium (IV) catalyst (R a ,S,S)-29, which was prepared in a similar procedure as to that of 26, demonstrated much more different reactivity for promoting the oxidative coupling reaction of 2-naphthols 27 (Scheme 14). An ESR study revealed no V-O-V linkage in the structure of (R a ,S,S)-29.…”
Section: -50mentioning
confidence: 95%
See 1 more Smart Citation
“…Related to Gong's catalyst 26, Sasai and coworkers [54][55][56][57] described dinuclear vanadium (IV) catalyst (R a ,S,S)-29, which was prepared in a similar procedure as to that of 26, demonstrated much more different reactivity for promoting the oxidative coupling reaction of 2-naphthols 27 (Scheme 14). An ESR study revealed no V-O-V linkage in the structure of (R a ,S,S)-29.…”
Section: -50mentioning
confidence: 95%
“…The two amino moieties in the catalyst affect the enantiocontrol of the coupling and the binaphthyl backone assists in aligning the two 2-naphthols with each other for the oxidative coupling. 57 Intermolecular manner coupling proceeds as a minor pathway.…”
Section: -50mentioning
confidence: 99%
“…Concentration and chromatography (hexane/etherϭ15/1) gave (R)-9 with 52% ee (0. 3 ), 62% ee) in acetone (4 ml) was added under reflux a solution of potassium permanganate (0.50 g, 3.17 mmol) in hot water (4 ml). After reflux for 1.5 h, the mixture was treated with 10% HCl (2 ml) and sodium bisulfite at room temperature, and then extracted with CHCl 3 (15 mlϫ3 (R)-1,1-Binaphthalene-2-carboxylic Acid BHA Ester ((؊)-(R)-9 with 62% ee) A mixture of above 1,1Ј-binaphthalene-2-carboxylic acid (83.9 mg, 0.28 mmol), pyridine (1 drop), and thionyl chloride (2 ml) was refluxed for 1.5 h, and then concentrated to afford acid chloride (0.11 g) as a yellow oil (IR (KBr): 1780).…”
Section: Methodsmentioning
confidence: 99%
“…Although we independently developed dinuclear vanadium(IV) catalysts and dinuclear vanadium(V) catalysts for enantioselective oxidative coupling of 2-naphthols, [44][45][46][47][48] the preparation procedure for dinuclear vanadium(IV) catalysts is similar to that of Gong's catalysts [66][67][68] except for the use of 2.0-2.2 eq of vanadyl sulfate in EtOH-tetrahydrofuran (THF)-H 2 O for the complexation. Even though the absolute configurations of the components of the catalysts are the same, the absolute configurations of the major products were opposite to each other (Table 5).…”
Section: Comparison Of Our Dinuclear Vanadium(iv) and (V) Catalysts Wmentioning
confidence: 99%
“…43) This review presents our recent research on development of chiral dinuclear vanadium complexes which work as dual activation catalysts for oxidative coupling of 2-naphthols. [44][45][46][47][48] The synthesis of optically pure 1,1Ј-bi-2-naphthol (BINOL) derivatives is of importance because these moieties are used as chiral ligands and auxiliaries for a wide range of organic functional transformations. 49,50) Catalytic asymmetric preparation of BINOL systems has continued to attract the attention of many researchers.…”
mentioning
confidence: 99%